Experience of the neonatal intensive care unit of the National research science center for maternal and child health - Tamara Chuvakova; Botakoz Abentaeva; Raushan Kamieva; Bibigul Charipova; Gaukhar Temirbaeva (National Scientific Medical Center, 2017)
The article presents the work results of Neonatal Intensive Care Unit of National Research Center for Maternal and Child Health. The main goal of the unit is to increase the survival rate of sick newborns, including premature babies. In addition, to minimize the possible complications that lead to increase in the number of people disabled since childhood and impair their quality of life. Realization of this purpose became possible with the introduction of eﬀective evidence-based medical care. As a result, for the period from 2008 to 2016, the survival rate of extremely low birth weight infants (500-999g) increased from 13% to 67% and very low body weight infants from 78% to 98% acordingly.